2014
DOI: 10.1007/s12011-014-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supranutritional Organic Selenium Supplementation on Postpartum Blood Micronutrients, Antioxidants, Metabolites, and Inflammation Biomarkers in Selenium-Replete Dairy Cows

Abstract: Dairy cows have increased nutritional requirements for antioxidants postpartum. Supranutritional organic Se supplementation may be beneficial because selenoproteins are involved in regulating oxidative stress and inflammation. Our objective was to determine whether feeding Se-yeast above requirements to Se-replete dairy cows during late gestation affects blood micronutrients, antioxidants, metabolites, and inflammation biomarkers postpartum. During the last 8-weeks before calving, dairy cows at a commercial fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 77 publications
3
30
0
6
Order By: Relevance
“…The cows which received Se-enriched yeast had greater Se concentrations in blood serum (32%), in colostrum DM (44%), and in milk DM (128%) than the cows fed equivalent doses of inorganic Se salts (100% established in the cows that received inorganic salts). The obtained results are consistent with those found in most studies in dairy cattle, showing that the cows receiving organic form of Se were characterized by higher concentrations of the mineral in blood serum (within the limits from 36 to 140%), in colostrum (up to 200%), and in milk (from 90 to 190%) compared with those receiving inorganic salts (Rowntree et al 2004;Weiss and Hogan 2005;Salman et al 2013;Hall et al 2014). The differences between the chemical forms of Se compounds in the diet-cow Se transmission may be due to the reactions that occur in the rumen environment.…”
Section: Diet-cow Se Transfer Efficiencysupporting
confidence: 90%
“…The cows which received Se-enriched yeast had greater Se concentrations in blood serum (32%), in colostrum DM (44%), and in milk DM (128%) than the cows fed equivalent doses of inorganic Se salts (100% established in the cows that received inorganic salts). The obtained results are consistent with those found in most studies in dairy cattle, showing that the cows receiving organic form of Se were characterized by higher concentrations of the mineral in blood serum (within the limits from 36 to 140%), in colostrum (up to 200%), and in milk (from 90 to 190%) compared with those receiving inorganic salts (Rowntree et al 2004;Weiss and Hogan 2005;Salman et al 2013;Hall et al 2014). The differences between the chemical forms of Se compounds in the diet-cow Se transmission may be due to the reactions that occur in the rumen environment.…”
Section: Diet-cow Se Transfer Efficiencysupporting
confidence: 90%
“…Nonetheless, all animals in the present study had adequate selenium levels at both time points. In dairy cows, selenium supplementation has been associated with better neutrophil function (Ibeagha et al, 2009), decreased prevalence of mammary infections (Erskine et al, 1987;Jukola et al, 1996), and improved antioxidant status and immune function (Hall et al, 2014). Studies that used supplementation of bovine mammary cells in vitro suggested that selenium supplementation plays a role in the optimization of udder health in via increased resistance to oxidative stress (Miranda et al, 2011).…”
Section: Variablementioning
confidence: 99%
“…Recent evidence suggested that supranutritional (higher than essential and optimum requirement) dietary Se may confer additional health benefits to animals (Hall et al., ; Hooper et al., ; Pappas, Zoidis, Papadomichelakis, & Fegeros, ). Therefore, now, Se supplementation in animal feeds is not just focused on the prevention of deficiency but benefiting health (Hu, McIntosh, & Young, ).…”
Section: Introductionmentioning
confidence: 99%